Effects of public reporting of prescription indicators on patient choices: evidence from propensity scores matching - Chen, Manli; Zhang, Xinping; Liu, Chaojie; Chen, Haihong; Wang, Dan; Liu, Chenxi (Frontiers in Pharmacology, 2023)
Background: Public reporting on health providers' performance (PRHPP) is increasingly used for empowering patients. This study aimed to test the effect of PRHPP using the theory of the consumer choice model.The study was conducted in 10 primary care institutions in Hubei province, China. Information related to the percentage of prescriptions requiring antibiotics, the percentage of prescriptions requiring injections, and average costs per prescription for each prescriber was calculated, ranked and displayed in a public place on a monthly basis. A questionnaire survey was undertaken on 302 patients 10 months after the initiation of the PRHPP, tapping into patient awareness, understanding, perceived value and use of the information in line with the theory of the consumer choice model. The fitness of data with the model was tested using structural equation modelling. The patients who were aware of the PRHPP were compared with those who were unaware of the PRHPP. The propensity score method (considering differences between the two groups of patients in age, gender, education, health and income) was used for estimating the effects of the PRHPP.Results: About 22% of respondents were aware of the PRHPP. Overall, the patients showed limited understanding, perceived value and use of the disclosed information.The data fit well into the consumer choice model. Awareness of the PRHPP was found to be associated with increased understanding of the antibiotic (p=0.028) and injection prescribing indictors (p=0.030). However, no significant differences in perceived value and use of the information (p>0.097) were found between those who were aware and those who were unaware of the PRHPP.Although PRHPP may improve patient understanding of the prescribing performance indicators, its impacts on patient choices are limited due to low levels of perceived value and use of information from patients. Additional support is needed to enable patients to make informed choices using the PRHPP.